Hydroa Vacciniforme with Eye Involvement: Report of Two Cases. Issue 1 (10th September 2014) - Mortazavi, Hossein; Hejazi, Pardis; Aghazadeh, Nessa; Esfandiari, Hamed; Ghanadan, Alireza; Jahanzad, Issa
Abstract We herein report two patients with hydroa vacciniforme and concomitant ophthalmic involvement, primarily in the form of keratoconjunctivitis leading to corneal opacity. Awareness of this occasional manifestation may help to prevent severe complications.